Bastar Dussehra: a unique cultural heritage - Sinha Roy, K. M.; Roshan, Rajesh; Kumar, Vijay (Bookwell in association with Anthropological Survey of India, Ministry of Culture, Government of India, 2019)
Study conducted in Bastar District of Chhattisgarh, India